An upgraded Tesla turbine concept for ORC applications. (1st September 2018) - Manfrida, G.; Pacini, L.; Talluri, L.
Abstract: The Tesla turbine is an original expander working on the principle of torque transmission by wall shear stress. The principle – demonstrated for air expanders at lab scale - has attractive features when applied to ORC expanders: it is suitable for handling limited flow rates (as is the case for machines in the range from 500 W to 5 kW), it can be developed to a reasonable size (rotor diameters between 0.1 and 0.3 m), with limited rotational speeds (from 1000 to 12000 rpm). The original concept is revisited, improving the stator layout (which is the main responsible for poor performance) and developing a modular design allowing to cover a wide power range, as well as to realize a perfectly sealed operation and including other fluid dynamics improvements. The flow model assumes complete real fluid behaviour, and includes several new concepts such as bladed channels for the stator and a detailed treatment of losses. Preliminary design sketches are presented and results discussed and evaluated. Several working fluids are considered, from refrigerants (R245fa, R134a, SES36) to hydrocarbons (n-Hexane, n-Pentane).